Analysis of Selling Price Determination using the Cost Plus Pricing Method Based on Full Costing at Bakmie Rica Top Tomohon - Veronika Putri Nirwono; Stanly W. Alexander; Djeini Maradesa (Journal of Finance and Business Digital, 2023)
The cost plus pricing method is a method of determining selling prices by adding up the cost of production plus a mark-up calculated based on the company's return on investment. The aim of this research is to analyze the selling price determined based on the full costing based cost plus pricing method compared to the selling price set by the company. The type of research used is descriptive qualitative. The research results show that there is a difference between the price set by the company and the selling price calculated using the cost plus pricing method. Of the 4 product samples used for research, there was a difference in that the price set by the company was lower than the cost plus pricing method.